Forex chartist companion : - Archer, Michael D. (Wiley, 2007)
In The Forex Chartist Companion, authors and active Forex traders Michael Archer and James Bickford provide a visual window into the behavior of the Forex market along with detailed information on the mechanics of day trading, market entry timing, and much more. With this book as your guide, you'll not only become familiar with innovative software and charting systems that provide a graphical interpretation of the markets, but you'll also discover how to instantly see patterns throughout those markets